Tutors' perceptions of ICTs in promoting computational thinking among pre-service teachers in Tanzanian colleges - Vicky Mrosso; Placidius Ndibalema; Abdon Ephrem (CTE Workshop Proceedings)
The current study explores tutors' perceptions of using information and communication technologies (ICTs) to develop computational thinking (CT) skills among pre-service teachers. The semi-structured interviews were conducted with purposively selected 4 principals and 20 tutors, and focus group discussions were held with 32 purposely selected pre-service teachers from 4 colleges, making a total of 56 participants. The findings revealed that tutors dominantly perceive CT as a digital literacy skill while ignoring the cognitive processes that underlie CT skills such as abstraction, algorithmic thinking, decomposition, and pattern recognition. Further, the findings show that tutors had limited understanding of identifying appropriate methods for developing CT, such as block-based programming tools. The study recommends that policymakers explicitly include CT and its aspects in the teacher education curriculum and conduct pilot testing of professional development training to foster CT skills using ICT among tutors.